Assessing gender differences in creative self-efficacy, creative ability and creative environment dimensions among lower secondary school students in Selangor, Malaysia / Adila Md Hashim, Sharipah Ruzaina Syed Aris and Chan Yuen Fook - Md Hashim, Adila; Syed Aris, Sharipah Ruzaina; Chan, Yuen Fook (Universiti Teknologi MARA, 2022)
This study aims to assess gender differences in creative self-efficacy, creative ability and creative environment dimensions among lower secondary school students in Selangor. A survey was conducted to empirically investigate the creativity differences between male and female students. A total of 374 lower secondary school students, consisting of 188 male and 186 female students, that were randomly selected from Form 1 and Form 2 classes from a secondary school in Selangor, Malaysia participated in this study. The creativity of students was assessed by a creativity level questionnaire instrument focused on three creativity dimensions; creative self-efficacy, creative ability, and creative environment. Data analysis showed that the overall creativity level between male and female students was almost the same (m=3.38, m= 3.42). Furthermore, the t-test analysis indicated no significant differences between genders in creative self-efficacy and creative ability dimensions, respectively. However, there was a significant difference identified in the creative environment dimension. Findings proved that gender differences did not affect the self-efficacy and ability of students in creativity except in a creative environment, which has a different impact on gender. Hence, educational institutions should pay attention to providing a conducive environment that might affect the creativity of the students.